A great legacy of muscle research and education from Dr. Sumiko Kimura. Issue 4 (12th June 2019) - Hanashima, Akira; Kawamura, Yuuki; Nakauchi, Yuni
Abstract: Dr. Sumiko Kimura, a former professor of biology at Chiba University, was known as a distinguished biochemist who contributed considerably to our knowledge about the cytoskeleton of muscle cells, especially through her work on connectin (also called titin) and actin regulatory proteins. Sadly, she suddenly passed away in Tokyo on November 1, 2018 at the age of 71. She succumbed to multiple organ failure caused by a bacterial infection following a third operation on her heart. Dr. Kimura had been continuing her research into connectin right up until several months before her decease.